Executive functioning and psychopathological profile in relatives of individuals with deficit v. non-deficit schizophrenia: a pilot study. (2nd April 2013) - Scala, S.; Lasalvia, A.; Seidman, L. J.; Cristofalo, D.; Bonetto, C.; Ruggeri, M.
Abstract : Aims: Heterogeneity of schizophrenia is known to be reflected in neuropsychological functioning of patients, but its expression in relatives is understudied. This study aims at exploring relationship between executive functioning and clinical profiles of first-degree relatives of patients who are classified as having or not having the deficit subtype of schizophrenia (DSRELs v. non-DSRELs), with the prediction of greater executive impairment in DSRELs. Methods: DSRELs ( n  = 15) and non-DSRELs ( n  = 40) were compared with community controls (CCs, n  = 55) on executive functioning measured by the Wisconsin Card Sorting Test (WCST) and the phonemic verbal fluency (PVF), and clinical measures. Effects of psychopathology and intelligence quotient (IQ) measures were investigated to determine their association with executive performance. Results: DSRELs showed more executive dysfunction on WCST and poorer social functioning than CCs and more severe negative symptoms than non-DSRELs. Differences on WCST-categories achieved (WCST-CA) remained significant after adjustment for clinical confounders and IQ. WCST-CA was associated with apathy and paranoid ideation only within the DSREL subgroup. Conclusions: Executive functioning and negative symptoms are severely impaired in first-degree relatives of deficit syndrome patients, thus suggesting that some neurocognitive deficits in patients may be transmitted within families according to the pathophysiology of the probands.